2005
DOI: 10.1073/pnas.0508932102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oligonucleotide sequences that direct the movement of the Escherichia coli FtsK translocase

Abstract: FtsK from Escherichia coli is a fast and sequence-directed DNA translocase with roles in chromosome dimer resolution, segregation, and decatenation. From the movement of single FtsK particles on defined DNA substrates and an analysis of skewed DNA sequences in bacteria, we identify GNGNAGGG, its complement, or both as a sequence motif that controls translocation directionality. GNGNAGGG is skewed so that it is predominantly on the leading strand of chromosomal replication. Translocation across this octamer fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
116
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 30 publications
4
116
1
Order By: Relevance
“…In addition, several studies have investigated how FtsK is guided toward dif through interactions with KOPS (7-9, 14, 18). Early reports suggested that FtsK could recognize KOPS during translocation, enabling it to reorient while translocating (7,8,14,19). However, other studies have suggested that KOPS acts only as a loading site for FtsK (9,13).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, several studies have investigated how FtsK is guided toward dif through interactions with KOPS (7-9, 14, 18). Early reports suggested that FtsK could recognize KOPS during translocation, enabling it to reorient while translocating (7,8,14,19). However, other studies have suggested that KOPS acts only as a loading site for FtsK (9,13).…”
mentioning
confidence: 99%
“…FtsK 50C is a DNA-dependent ATPase, which can activate XerCDdif recombination (6). Single-molecule studies have shown that FtsK 50C translocates at ≈5 kb s −1 and resists stalling at forces up to 65 pN (8,12,13,17). In addition, several studies have investigated how FtsK is guided toward dif through interactions with KOPS (7-9, 14, 18).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The pore size of the FtsK hexameric ring in the crystal structure is ∼30 Å. Doublestranded DNA could easily be threaded through this annulus, but proteins associated with the DNA might not be accommodated. In vitro experiments with the cytoplasmic motor domains of FtsK and SpoIIIE indicate that these enzymes can displace ssDNA when it encounters a DNA triplex (Bigot et al 2005;Levy et al 2005;Ptacin et al 2008), suggesting that DNA-binding proteins might also be stripped off. However, some DNA-binding proteins have very high affinity for their cognate binding sites.…”
mentioning
confidence: 99%